Physiological and toxicological response of Microcystis aeruginosa BCCUSP232 exposed to Salvinia auriculata extracts - da Silva, Regildo Márcio Gonçalves [UNESP]; Lourenção, Anderson [UNESP]; Franciscatti Mecina, Gustavo [UNESP]; Cordeiro-Araújo, Micheline Kézia; Bittencourt-Oliveira, Maria Do Carmo; Ahii Chia, Mathias; Granero, Filipe Oiveira [UNESP]; Malaguti Figueiredo, Célia Cristina [UNESP]; Pompermayer Machado, Levi [UNESP]; Pereira Silva, Luciana (Taylor & Francis, 2024)
Microcystis aeruginosa is one of the most predominant freshwater bloom-forming cyanobacterium found globally which is capable of producing toxic secondary metabolites including microcystins that might intoxicate animals and humans when contaminated water or food is ingested. Salvinia auriculata Aubl is one of the plants that might possess bioactive compounds capable of controlling growth and reproduction of M. aeruginosa. The present study aimed to determine the presence of bioactive compounds in S. auriculata extracts and determine alterations occurred in growth and reproduction of M. aeruginosa when exposed to these plant extracts. In addition, this investigation aimed to examine the influence of S. auriculata on antioxidant enzymes detected in M. aeruginosa. The results obtained demonstrated that the aqueous and ethanolic extracts of S. auriculata presented potential for control of cyanobacteria populations, exhibiting algicidal action on M. aeruginosa as well as interfering in antioxidant enzymes activities and parameters associated with oxidative stress. Phytochemical analyses demonstrated the presence of polyphenols and flavonoids content in both extracts. In addition, application of S. auriculata extracts did not produce cytogenotoxicity and/or mutagenicity utilizing Allium cepa test. Therefore, further studies are needed in order to identify and characterize the compounds responsible for these effects on M. aeruginosa and provide information regarding the possible application of S. auriculata in the treatment of drinking water.
Keywords: Algicidal; cyanobacteria; cyanotoxins; genotoxicity; microcystis aeruginosa; oxidative stress; salvinia auriculata